Accessing and Understanding Heritage Buildings through ICT. The INCEPTION Methodology Applied to the Istituto degli Innocenti. Issue 6 (3rd June 2021) - Maietti, Federica; Di Giulio, R.; Medici, M.; Ferrari, F.; Piaia, E.; Brunoro, S.
ABSTRACT: Nowadays ICT and digital heritage play an essential role in accessing and understanding Europe's cultural basis and history. Documentation, data processing and representation of Architectural Heritage through digital models are one of the main challenges for knowledge, conservation, management and inclusive use of European heritage assets. The project INCEPTION — Inclusive Cultural Heritage in Europe through 3D semantic modelling has developed in this direction. The overall INCEPTION methodology is explained starting from one of the nine Demonstration Cases developed under the project: the Italian Demonstration Case, the Istituto degli Innocenti in Florence, by Brunelleschi, is an outstanding example of the overall INCEPTION process in the digital documentation, interpretation and deployment. A common framework for integrating different expertise, an advanced methodology for integrated data capturing, semantic modelling in BIM environment and the development of a platform to collect, archive and share semantically enriched models and applications for models deployment are the main project steps.